2020
DOI: 10.20900/immunometab20200034
|View full text |Cite
|
Sign up to set email alerts
|

Fat and Iron Don't Mix

Abstract: Low-grade chronic adipose tissue (AT) inflammation is now recognized as a pivotal driver of the multi-organ dysfunction associated with obesity-related complications; and adipose tissue macrophages (ATMs) are key to the development of this inflammatory milieu. Along with their role in immunosurveillance, ATMs are central regulators of AT iron homeostasis. Under optimal conditions, ATMs maintain a proper homeostatic balance of iron in adipocytes; however, during obesity, this relationship is altered, and iron i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The fact that serum TF, largely derived from liver, and hepatic expression of TF were unaffected by the polymorphisms in humans (1) suggests that adipocyte TF does not play a role in whole-body iron regulation, but rather may be playing a paracrine role in adipose tissue and mediating local iron trafficking. Consistent with this hypothesis, work from Dr. Hasty's laboratory has demonstrated delivery of iron from macrophages to adipocytes within adipose tissue upon highfat feeding, a process that is also associated with macrophage polarization (26). Other investigators have shown expression of the transferrin receptor in adipocytes is required for normal differentiation and thermogenesis (27).…”
Section: Discussionmentioning
confidence: 93%
“…The fact that serum TF, largely derived from liver, and hepatic expression of TF were unaffected by the polymorphisms in humans (1) suggests that adipocyte TF does not play a role in whole-body iron regulation, but rather may be playing a paracrine role in adipose tissue and mediating local iron trafficking. Consistent with this hypothesis, work from Dr. Hasty's laboratory has demonstrated delivery of iron from macrophages to adipocytes within adipose tissue upon highfat feeding, a process that is also associated with macrophage polarization (26). Other investigators have shown expression of the transferrin receptor in adipocytes is required for normal differentiation and thermogenesis (27).…”
Section: Discussionmentioning
confidence: 93%
“…Iron accumulation is closely related to cell senescence [ 14 ]. The iron contents in the adipose tissues of obese individuals are significantly higher than those in the adipose tissues of individuals with normal weights [ 15 ]. Therefore, we examined the expression levels of iron metabolism-related genes in adipocytes and ASCs, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding mediators that regulate iron demands in these different cell types, tissueresident macrophages may play a role in modulating local iron availability. 53,68 Tissue iron accumulation can have a harmful effect, making the body more vulnerable to ferroptosis, a pro-inflammatory and irondependent cell death process triggered by excess iron and ROS. An example of this is seen in cases of frataxin deficiency, where a significant reduction in the synthesis of iron-sulfur clusters within mitochondria disrupts the activity of mitochondrial respiratory chain complexes and aconitase.…”
Section: Iron As a Regulator Of Thermogenesismentioning
confidence: 99%
“…While iron uptake is necessary for the differentiation of white, beige, and brown adipocytes, as well as for maintaining increased mitochondrial activity in thermogenic adipocytes, reducing intracellular and mitochondrial iron levels allows for optimal and improved function in mature white adipocytes. Regarding mediators that regulate iron demands in these different cell types, tissue‐resident macrophages may play a role in modulating local iron availability 53,68 …”
Section: Introductionmentioning
confidence: 99%